Comparison of two strategies for assessing critical walking velocity - Leandro Quadro Corrêa; Airton José Rombaldi; Paula Aver Bretanha Ribeiro; Eduardo Kokubun (Universidade Federal de Santa Catarina, 2009)
The aim of this study was to compare two strategies of walking test performance (self-paced intensity and fixed pace) for the determination of critical walking velocity (CWV) parameters. Fourteen female volunteers (age = 60.8 ± 10.3 years) were randomly submitted to three fixed-time walking tests (3, 6 and 9 minutes) and three fixed-pace tests ranging from 10 to 15 seconds at intervals of 20 meters. These predictive tests were used to calculate CWV. The mean standard error of the CWV estimate was 4.96% for the fixed-pace strategy, and 2.98% for the fixed-time strategy, corresponding to an adequate estimation. The results showed a high correlation between strategies (r=0.73; p < 0.01). The mean coefficient of determination was R2 = 0.98 ± 0.03 for the fixed-pace model and R2 = 0.99 ± 0.002 for the self-paced model. ANCOVA for the predictive tests showed no differences between strategies (p=0.29), subjects x strategies (p=0.29), or strategies x time (p=0.26). Geometric regression comparing the fixed-time x fixed-pace strategies (1.42 ± 0.14 and 1.38 ± 0.21 m/s) or the Bland-Altman method revealed no differences between performance strategies. We conclude that the two strategies were equivalent for the evaluation of performance in the sample studied.